Assessment of cfDNA Levels in Saliva Samples of Stressed Young Adults: Preliminary Study - Ekin Çelik; Miraç Berkay Köksal; Hacı Mehmet Akbulut; Selahattin Ata Aydın; Yiğit Emre Kurt; Can Okan; Simay Çetinkaya (Ahi Evran Medical Journal)
Purpose: The aim of this pilot study was to examine the levels of cell-free DNA (cfDNA) in the saliva samples of second-year medical students before and after a stress-inducing event, exams.